On Periodic Solutions of Higher-Order Functional Differential Equations. (3rd February 2008) - Kiguradze, I.; Partsvania, N.; Půža, B.
Abstract : For higher-order functional differential equations and, particularly, for nonautonomous differential equations with deviated arguments, new sufficient conditions for the existence and uniqueness of a periodic solution are established.